2013
DOI: 10.5114/jcb.2013.34451
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal urethral brachytherapy for recurrence of transitional cell carcinoma of urinary bladder in urethral stump

Abstract: We report a unique case of successfully performed intraluminal brachytherapy for low volume urethral mucosal recurrence of transitional cell carcinoma urinary bladder, initially treated by transurethral resection of bladder tumor, followed by radical cystectomy. Since the patient was unwilling to undergo any other operational interventions, intraluminal brachytherapy of urethra was attempted. Fluroscopy guided intraluminal HDR brachytherapy using Lumencath® catheter under local anesthesia, and remote afterload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…There are only two case reports on the use of a Lumencath applicator in intraluminal BT for treating the male urethra. Chakrabarti et al reported complete tumor remission and no sever late toxicity using a fraction dose of 7 Gy in seven weekly fractions was prescribed at 5 mm from the Lumencath applicator [24]. Lewis et al demonstrated intraluminal HDR-BT prescribed with 36 Gy in nine fractions followed by a boost of 24 Gy in six fractions [25].…”
Section: Discussionmentioning
confidence: 99%
“…There are only two case reports on the use of a Lumencath applicator in intraluminal BT for treating the male urethra. Chakrabarti et al reported complete tumor remission and no sever late toxicity using a fraction dose of 7 Gy in seven weekly fractions was prescribed at 5 mm from the Lumencath applicator [24]. Lewis et al demonstrated intraluminal HDR-BT prescribed with 36 Gy in nine fractions followed by a boost of 24 Gy in six fractions [25].…”
Section: Discussionmentioning
confidence: 99%
“…The dose prescribed was 7 Gy in seven weekly fractions at 0.5 cm from the single applicator. Patient had complete regression of the lesion at 1 year post treatment [ 13 ]. Dalbagni et al .…”
Section: Discussionmentioning
confidence: 99%
“…The patient remained asymptomatic and disease-free at a year past treatment. 16 Lewis et al present a case of a male patient with primary clear-cell adenocarcinoma of the urethra treated using intraluminal brachytherapy with 9 daily fractions of 4 Gy each, up to a total radiation dose of 36 Gy. Although the patient was asymptomatic 2 months after treatment, irregular urethral wall thickening was seen in magnetic resonance images, and the patient received an additional dose of 24 Gy divided in 6 fractions of 4 Gy.…”
Section: Chronic Irritation Aftermentioning
confidence: 99%